Simplified quantification of 5-HT2A receptors in the human brain with [11C]MDL 100,907 PET and non-invasive kinetic analyses. - Meyer, P; Bhagwagar, Z; Cowen, P; Cunningham, V; Grasby, P; Hinz, R (2010)
BACKGROUND: [(11)C]MDL100,907 is a promising positron emission tomography (PET) ligand for 5-HT(2A) receptor quantification in vivo. Studies suggest that [(11)C]MDL100,907 PET may be quantified by non-invasive reference tissue analyses using cerebellum as reference region. We systematically investigated the validity of such analyses. METHODS: Five healthy volunteers underwent [(11)C]MDL100,907 PET at baseline and after mirtazapine pre-treatment. Regional time-activity curves of 10 regions of interest (ROI) were analyzed for binding potential (BP(ND)) and mirtazapine receptor occupancy (Occ) using: simplified reference tissue model (SRTM), multi-linear reference tissue model (MRTM), their two-parameter versions (SRTM2/MRTM2), non-invasive graphical analysis (NIGA) and a tissue activity concentration ratio. NIGA was also applied voxel-wise to generate BP(ND) maps. These methods were compared with a two-tissue compartment model with arterial input function (2TCM) Results: SRTM and MRTM frequently failed to yield reliable results. SRTM2 and MRTM2 gave virtually identical estimates of BP(ND), which were highly correlated with 2TCM analyses (R(2)>or=0.86) although with negative bias (-29+/-27% at baseline across all ROI). NIGA was less biased (-19+/-16%) and better correlated with 2TCM (R(2)>or=0.93). Regarding Occ, NIGA and SRTM2/MRTM2 showed comparable mean biases (-11+/-27% vs. -7+/-47%) but correlation with 2TCM was higher for NIGA (R(2)=0.90 vs. 0.77). NIGA parametric maps (analysed using identical ROI) resulted in moderate bias in BP(ND) (-26+/-22%; R(2)>or=0.88) and Occ (-17+/-36%; R(2)=0.78). Estimates obtained from tissue ratios performed least favourably. CONCLUSIONS: NIGA is well suited for analysis of [(11)C]MDL100,907 PET studies, yielding estimates of 5-HT(2A) receptor availability and changes that are highly correlated with results from invasive 2TCM analyses. This should greatly enhance the applicability of 5-HT(2A) receptor PET studies.